1995
DOI: 10.1002/eji.1830250824
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reactive T cell clones in a restricted population of interleukin‐2 receptor β+ cells expressing intermediate levels of the T cell receptor in the liver and other immune organs

Abstract: T cells expressing high levels of the T cell receptor (TCRhigh) differentiate in the major intrathymic pathway and then distribute to the peripheral immune organs, whereas T cells expressing intermediate levels of the TCR (TCRint) differentiate in both extrathymic pathways and an alternative intrathymic pathway and localize in unique sites, including the liver and thymic medulla. Since TCRint cells constitutively express interleukin-2 receptor beta-chain (IL-2R beta), two-color staining for CD3 (or TCR) and IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
1

Year Published

1996
1996
2001
2001

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 38 publications
1
57
1
Order By: Relevance
“…Both subsets of CD3 int cells comprise self-reactive forbidden clones in the Mls system [25,26]. In a recent study, we proposed the possibility that NK1.1 + CD3 int cells in mice correspond to CD56 + T cells in humans while NK1.1 − CD3 int cells in mice correspond to CD57 + T cells in humans [27,28].…”
Section: Discussionmentioning
confidence: 98%
“…Both subsets of CD3 int cells comprise self-reactive forbidden clones in the Mls system [25,26]. In a recent study, we proposed the possibility that NK1.1 + CD3 int cells in mice correspond to CD56 + T cells in humans while NK1.1 − CD3 int cells in mice correspond to CD57 + T cells in humans [27,28].…”
Section: Discussionmentioning
confidence: 98%
“…We previously showed the distinct functional properties of extrathymic T cells and thymus-derived T cells. Namely, extrathymic T cells (TCR int cells) eliminate abnormal self-cells (mainly self-antigens in the context of monomorphic major histocompatibility complex antigen) because of their autoreactivity (i.e., innate immunity), [21][22][23][24] whereas thymus-derived T cells (TCR high cells) interact with foreign antigens (mainly in the FIG. 7.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] In the case of mice, these extrathymic T cells are estimated to be interleukin 2R ␤-chain ϩ (IL-2R␤) intermediate CD3 (CD3 int ) cells, according to their constitutive expression of IL-2R␤ and the low density of TCR-CD3 complex (i.e., intermediate CD3 or CD3 int ) on the surface. Subsequently, we reported that IL-2R␤ ϩ CD3 int cells consist of both natural killer 1.1 ϩ (NK1.1 ϩ ) and NK1.1 Ϫ subsets at a ratio of approximately 1:1 in the liver.…”
mentioning
confidence: 99%